Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.ttbdis.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterization of spotted fever group rickettsiae in ticks from Central Italy

Abstract: The aim of this study was to investigate the presence of rickettsial pathogens in ticks from Central Italy. A total of 113 ticks hailed from Latium and Tuscany regions were identified and tested by PCR to detect gltA, ompA, ompB genes of Rickettsia. Positive amplicons were sequenced and identified at species level. Ticks were analyzed individually or in pools. The percentage of positivity for SFG rickettsiae was 12.4%, expressed as minimum infection rate (MIR) assuming that one tick was positive in each positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
5
15
2
2
Order By: Relevance
“…In our study, R. helvetica was identified exclusively in I. ricinus pools (two) which are the main vector and natural reservoir [1], while R. monacensis was found mainly in I. ricinus pools (35 out of 38), with one positive in D. marginatus, R. sanguineus and Hae. punctata-the latter is similar to the finding of Scarpulla and collaborators [12]. These findings suggest that, even if the circulation in the environment is mainly maintained by I. ricinus, there may be other species implicated in the transmission or R. monacensis as suggested by Madeddu and collaborators [28].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In our study, R. helvetica was identified exclusively in I. ricinus pools (two) which are the main vector and natural reservoir [1], while R. monacensis was found mainly in I. ricinus pools (35 out of 38), with one positive in D. marginatus, R. sanguineus and Hae. punctata-the latter is similar to the finding of Scarpulla and collaborators [12]. These findings suggest that, even if the circulation in the environment is mainly maintained by I. ricinus, there may be other species implicated in the transmission or R. monacensis as suggested by Madeddu and collaborators [28].…”
Section: Discussionsupporting
confidence: 85%
“…In our study, eight SFG Rickettsia species have been identified in ticks: R. slovaca, R. monacensis, R. massiliae, R. conorii, R. aeschlimannii, R. helvetica, R. raoultii, and R. felis. The findings on Rickettsia species of our study not completely overlap with the findings of similar studies carried out by Scarpulla and collaborators [12] in Tuscany, Maioli and collaborators [11] in Emilia Romagna, and Chisu and collaborators [26] in Sardinia. R. monacensis the second most representative species in our study was the most frequent species in Tuscany [12], and previously in Emilia Romagna [11], while it was not detected in Sardinia [26].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations